MODEL PENGADAAN LAHAN UNTUK RUANG TERBUKA HIJAU (RTH) KOTA SIGLI - Muhammad Khaled; Muhammad Isya; Ashfa Achmad (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
Green Open Space (RTH) in urban areas has value for the needs and needs of parks and recreation. The allocation of twenty percent of public green open space from the urban area of Sigli City as stipulated in the Pidie Regency Qanun Number 5 of 2014 concerning the Pidie Regency Spatial Plan for 2014-2034 has not yet been achieved. This study aims to examine the factors that influence land acquisition and how land acquisition models are appropriate for public green space in the city of Sigli. This research uses quantitative methods. The data obtained in the form of ordinal data and nominal dichotomos. The data was analyzed by logistic regression methods and Focused Group Discussion (FGD). The model of the logistic regression equation formed is: "Ln" ("p" / "1-p") "= -8,407 + 0,894" "X" _ "1" "+ 2,192" "X" _ "2" "+ 0,346" "X" _ "3" "+ 0.712" "X" _ "4" + "0.144" "X" _ "5" - "1,072" "X" _6- "0.526" "X" _ "7" The results of logistic regression analysis obtained two factors that most influence on land acquisition for green space in the city of Sigli, namely the SKPK (X2) program and local wisdom (X6). Factors influencing the results of the logistic regression analysis are then discussed in the FGD. The FGD came to the conclusion that the land acquisition strategy for green space in the City of Sigli cannot rely solely on the budget on the SKPK program. Land acquisition for green space can also be done using village funds and Corporate Social Responsibility (CSR) funds.